Lacunary Sequence Spaces of Interval Numbers: Ayhan Esi - Team, Support (Thai Journal of Mathematics, 2012)
In this paper we introduce the concept of lacunary strongly convergence and lacunary statistical convergence of interval numbers. We prove some inclusion relations and study some of their properties.